2022
DOI: 10.1002/ejhf.2650
|View full text |Cite
|
Sign up to set email alerts
|

Atrial amyloidosis: mechanisms and clinical manifestations

Abstract: Cardiac amyloidosis (CA) is now recognized as an important cause of heart failure. Increased wall thickness and diastolic dysfunction of the left ventricle are the most easily detectable manifestations of CA, but amyloid accumulates in all cardiac structures. Involvement of the left and right atria may be due to the haemodynamic effects of ventricular diastolic dysfunction, the effects of amyloid infiltration into the atrial wall, and the cardiotoxic damage of atrial cardiomyocytes by amyloid precursors. Atria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…AANP amyloid deposits in the atrium, often referred to as isolated atrial amyloidosis (IAA) [ 8 , 9 ], have been reported in surgically resected appendages and autopsy studies [ 4 , 10 16 ]; however, very few histologically reports of ATTR amyloid in the atrium are published [ 4 , 10 12 ]. Further, most previous studies were limited to evaluation of the atrium and did not evaluate the ventricles or other cardiac structures.…”
Section: Discussionmentioning
confidence: 99%
“…AANP amyloid deposits in the atrium, often referred to as isolated atrial amyloidosis (IAA) [ 8 , 9 ], have been reported in surgically resected appendages and autopsy studies [ 4 , 10 16 ]; however, very few histologically reports of ATTR amyloid in the atrium are published [ 4 , 10 12 ]. Further, most previous studies were limited to evaluation of the atrium and did not evaluate the ventricles or other cardiac structures.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of atrial dysfunction and enlargement, patients with ATTR-CA have a higher risk of left atrial thrombosis even when in SR. This may also be related to the amyloid deposition into the atrial wall, and the cardiotoxic damage of atrial cardiomyocytes by amyloid precursors ( 77 ). Among patients with CA and AF/atrial flutter, anticoagulation is indicated regardless of CHA2DS2-VASc score as in these patients it is not associated with the probability of LAA thrombosis.…”
Section: Attr Symptomatic Treatmentmentioning
confidence: 99%
“…Isolated right or left atrial CA is related to atrial natriuretic peptide overproduction and has been found in about 50% of patients by Sukhacheva et al [ 28 , 29 ].…”
Section: Pathophysiology and Clinical Features Of The Right Involveme...mentioning
confidence: 99%